Importance of Esophageal pH monitoring and manometry in the preoperative evaluation for bariatric surgery to determine the surgical technique (Research, Society and Development, 2026)
Obesity is a chronic disease with a high global prevalence and is frequently associated with Gastroesophageal Reflux Disease (GERD), a condition that may interfere with the outcomes of bariatric surgery. Therefore, adequate preoperative evaluation becomes essential for selecting the most appropriate surgical technique and preventing postoperative complications. This study aimed to evaluate the importance of esophageal pH monitoring and esophageal manometry in the preoperative evaluation of obese patients undergoing bariatric surgery, correlating body mass index (BMI), the DeMeester score, and the presence of gastroesophageal reflux symptoms. This is a retrospective cross-sectional observational study based on the analysis of secondary data obtained from medical records of patients who underwent bariatric surgery in a general surgery department in the city of Rio de Janeiro between 2015 and 2022. A total of 252 medical records were analyzed, considering variables such as sex, surgical technique, presence of reflux symptoms, and the results of esophageal pH monitoring and esophageal manometry. The results demonstrated a predominance of female patients and vertical sleeve gastrectomy as the most frequently performed surgical technique. A significant proportion of patients presented pathological acid reflux detected by pH monitoring, even in the absence of clinical symptoms, as well as esophageal motility disorders identified through manometry. It is concluded that esophageal pH monitoring and esophageal manometry are fundamental tools in the preoperative evaluation of bariatric surgery, contributing to the individualized selection of the surgical technique, reduction of GERD-related complications, and improvement of clinical outcomes and patients’ quality of life.